DOES ORTHODONTICS EXTRACTIONS NEGATIVELY AFFECT THE OCCLUSAL BITE FORCE OF AN INDIVIDUAL - A QUASI-EXPERIMENTAL STUDY - Shabbir, Sadia; Ali, Batool (Journal of Ayub Medical College Abbottabad, 2022)
Background: Orthodontics is said to be that branch of dentistry which takes into consideration the facial growth, dentition development as well as occlusion. It is also concerned with the prevention as well as the rectification of the occlusal anomalies. The aim of this study was to determine the occlusal bite force (OBF) changes during fixed orthodontic treatment up to a period of 9 month in Class I patients treated with extraction and non-extraction treatment protocol. Methods: It was a Quasi-experimental study conducted from 13th March 2018 to 20th March 2019 in the orthodontic department on 90 subjects which were divided into a treatment group extraction (30), non-extraction (30) and controls (n=30). Bite force was measured with an OBF gauge at 6 different intervals before starting the treatment to the ninth month of the treatment. The changes in OBF were assessed using r-ANOVA test. Post-hoc Bonferroni was used for multiple comparisons in bite force levels at different treatment stages. The mean difference in OBF between treatment groups was evaluated by independent t-test. Significance for all tests was predetermined at p value of ‰¤0.05. Result: The mean OBF significantly increased in both the extraction and non-extraction treatment groups (p<0.001) in comparison to the controls. The mean change in OBF was comparatively greater in the non-extraction group as opposed to the extraction group, but the difference was not statistically significant (p=0.468) Conclusion: Orthodontic treatment has a positive effect with a gradual increase in the OBF values in subjects treated with extraction and non-extraction fixed mechano-therapy. This indicates that well-aligned arches can have an impact on the functional occlusion, hence, enhancing the bite force levels.